Entrepreneurship Education through Training in Making Aromatherapy Candles and Natural Soap Made from Eucalyptus Oil (Melaleuca Leucadendron) at Wonoharjo Village, Boyolali Regency - Permatasari, Putri; Faiz, Imaduddin Muhammad; Nawandini, Silvia; Rayhani, Wulida; Putri, Desinta Yulyana; Zayyan, Evan; Kambuaya, Gideon Ezra; Nugroho, Feberian; Hanafi, Hamzah (Jurnal Ilmiah Mandala Education (JIME), 2024)
Wonoharjo Village has the potential to support the village government to develop economic activities. The village has the potential for local eucalyptus oil, which is used as one of the villagers' economic resources. However, no product innovation has been developed so that the selling power of the community is still low. Students of KKN Research Group 19, Sebelas Maret University Surakarta in 2024, initiated entrepreneurship education through training in making aromatherapy candles and natural soap with essential oil additives in the form of eucalyptus oil in Wonoharjo Village, Kemusu, Boyolali, Central Java. The women participating in the PKK Wonoharjo Village participated enthusiastically in the training on the utilization of eucalyptus oil into high-value products such as aromatherapy candles and natural soap. Aromatherapy candles and natural soaps are natural products used for health purposes and protection of the body so that it is expected to be able to increase the selling power of the community through existing competenciesDesa Wonoharjo memiliki potensi yang menjadi daya dukung bagi pemerintahan desa untuk dapat dikembangkan menjadi kegiatan ekonomi. Desa ini memiliki potensi minyak kayu putih lokalnya yang dijadikan sebagai salah satu sumber ekonomi warga desa. Namun, belum ada inovasi produk yang dikembangkan sehingga daya jual masyarakat masih rendah. Mahasiswa KKN Grup Riset Kelompok 19 Universitas Sebelas Maret Surakarta tahun 2024, menginisiasi pendidikan kewirausahaan melalui pelatihan pembuatan lilin aromaterapi dan sabun natural dengan bahan tambahan minyak esensial berupa minyak kayu putih di Desa Wonoharjo, Kemusu, Boyolali, Jawa Tengah. Ibu-ibu peserta PKK Desa Wonoharjo mengikuti dengan cukup antusias pelatihan pemanfaatan minyak kayu putih menjadi produk bernilai guna tinggi seperti lilin aromaterapi dan sabun natural. Lilin aromaterapi dan sabun natural merupakan produk alami yang digunakan untuk keperluan kesehatan dan perlindungan pada tubuh sehingga diharapkan mampu meningkatkan daya jual masyarakat melalui otensi yang ada.